Comparison of different plasmonic nanograting profiles for quality light absorption in nanostructured metal-semiconductor-metal photodetectors - Masouleh, F.; Das, Narottam; Mashayekhi, H. (The Society of Photo-Optical Instrumentation Engineers, 2013)
We have demonstrated the possibility of quality light absorption in plasmonic nanostructured metal-semiconductor-metal (MSM) photodetectors with different groove shapes and analyzed the device performance by varying the physical parameters. The simulations revealed the quality light absorption for various nanogratings. The MSM photodetectors (MSM-PDs) utilizing nanostructure fabrication enable future high-speed devices to achieve high-responsivity bandwidth product. Finite difference time-domain method is used to evaluate the quality light absorption by plasmonics one dimensional nanostructures with the illumination of transverse magnetic light, since the surface plasmon polariton excitation is polarization sensitive. In our modeling, various nanograting profiles incorporated on the conventional MSM-PDs perform in different ways to improve the light absorption capacity in the subwavelength aperture region of the device. Therefore, the grooves’ shape and size are the effective parameters to enhance the light concentration below the diffraction limit. The simulation results demonstrated the light absorption enhancement of ~ 33.6 times for newly introduced nonlinearly tapered (or trapezoidal) ellipse wall nanogratings with the aid of plasmonic nanogratings effects.